Early morbidity profile of late preterm neonates in a teaching hospital in South India - Raja, J Ashok (Indian Journal of Child Health, 2020)
Background: Late preterm neonates although close to term neonates in weight and physical appearance, have a high risk for morbidities causing a significant health care cost. Objective: We undertook the study to analyze the morbidity pattern of late preterm infants to help in better management of these neonates. Materials and Methods: This was a retrospective analytical study conducted in a tertiary hospital of South India. The data were retrieved from admission, discharge registers, case records, and neonatal database. The rate of various morbidities during the hospital stay and subgroup analysis was performed. Results: About 936 late preterm neonates (32.8% of preterm deliveries) were admitted in neonatology ward for various morbidities. The mean gestational age was 35.32±0.76 (1 SD) and mean birth weight was 2.11±0.46 kg (1 SD). Male:female ratio was 1.12:1. About 50% of them were born at 36 weeks, 31% at 35 weeks, and 18% were born at 34 weeks. About 16.72% of admitted late preterm neonates were severe intrauterine growth restriction (IUGR). Neonatal jaundice requiring phototherapy 33.1%, sepsis 23.7%, birth asphyxia 8.3%, and respiratory distress syndrome 6.62%, were the most common morbidities. Around 14.2% of admitted neonates required some form of respiratory support. Sepsis occurred in a significant proportion (23.7%) and 18.7% of admitted neonates had hypoglycemia. The average duration of stay was 8.19±5.5 (SD) days. Conclusion: Late preterm neonates are at a high risk for various morbidities, neonatal jaundice, respiratory distress, asphyxia, sepsis, and required prolonged stay. A high proportion of severe IUGR was found in our study.